Sex-Specific and Strain-Dependent Effects of Early Life Adversity on Behavioral and Epigenetic Outcomes - Kundakovic, Marija; Lim, Sean; Gudsnuk, Kathryn; Champagne, Frances A. (Frontiers in Psychiatry, 2013)
Early life adversity can have a significant long-term impact with implications for the emergence of psychopathology. Disruption to mother-infant interactions is a form of early life adversity that may, in particular, have profound programming effects on the developing brain. However, despite converging evidence from human and animal studies, the precise mechanistic pathways underlying adversity-associated neurobehavioral changes has yet to be elucidated. One approach to the study of mechanism is exploration of epigenetic changes associated with early life experience. In the current study, we examined the effects of postnatal maternal separation in mice and assessed the behavioral, brain gene expression, and epigenetic effects of this manipulation in offspring. Importantly, we included two different mouse strains (B6 and Balb/c) and both male and female offspring to determine strain- and/or sex-associated differential response to maternal separation. We found both strain-specific and sex-dependent effects of maternal separation in early adolescent offspring on measures on open-field exploration, sucrose preference, and social behavior. Analyses of cortical and hippocampal mRNA levels of the glucocorticoid receptor (Nr3c1) and brain-derived neurotrophic factor (Bdnf) genes revealed decreased hippocampal Bdnf expression in maternally-separated B6 females and increased cortical Bdnf expression in maternally separated male and female Balb/c offspring. Analyses of Nr3c1and Bdnf (IV and IX) CpG methylation indicated increased hippocampal Nr3c1 methylation in maternally separated B6 males and increased hippocampal Bdnf IX methylation in male and female maternally separated Balb/c mice. Overall, though effect sizes were modest, these findings suggest a complex interaction between early life adversity, genetic background, and sex in the determination of neurobehavioral and epigenetic outcomes that may account for differential vulnerability to later life disorder.